2005
DOI: 10.1021/jp054304p
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Study of the Thermodynamic Properties of Calcium Apatites. 1. Hexagonal Phases

Abstract: Structural and thermodynamic properties of crystal hexagonal calcium apatites, Ca10(PO4)6(X)2 (X = OH, F, Cl, Br), were investigated using an all-atom Born-Huggins-Mayer potential by a molecular dynamics technique. The accuracy of the model at room temperature and atmospheric pressure was checked against crystal structural data, with maximum deviations of ca. 4% for the haloapatites and 8% for hydroxyapatite. The standard molar lattice enthalpy, delta(lat)H298(o), of the apatites was calculated and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 50 publications
6
33
0
1
Order By: Relevance
“…It may be noted at this point that some authors have attempted to estimate apatites thermodynamic properties based on lattice energy computational estimations and molecular modeling calculations [30,61,86]. However, the outcomes of these computed methods sometimes deserve to be debated as they do not always agree well with experimental facts.…”
Section: Application Of Additive Estimation Methods To the Case Of Phmentioning
confidence: 99%
“…It may be noted at this point that some authors have attempted to estimate apatites thermodynamic properties based on lattice energy computational estimations and molecular modeling calculations [30,61,86]. However, the outcomes of these computed methods sometimes deserve to be debated as they do not always agree well with experimental facts.…”
Section: Application Of Additive Estimation Methods To the Case Of Phmentioning
confidence: 99%
“…Although they considered the phosphate ion to be a rigid tetrahedron, they were able to reproduce the experimental crystal parameters with a maximum error of 1%. We have also found that such an assumption gives a good account of the physical properties of solid apatites under compression [12,13].…”
Section: Introductionmentioning
confidence: 64%
“…The experimental results were interpreted using a correlation with the enthalpy of formation of the species CaX 2 (X = OH − , F − , Cl − , and Br − ), allowing for the estimate of the standard molar enthalpy of formation of iodapatite (IAp), which had not been determined before. Later, the thermodynamic properties of the entire family of hexagonal [12] and monoclinic (P2 1 /b) [13] calcium apatites (hydroxy-, fluor-, chlor-, and bromapatite) were studied using the molecular dynamics technique (MD). The structural and energetic model employed reproduced well the experimental crystal data, and the standard molar lattice enthalpies calculated by the MD technique showed a good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason for the lower degree of fusion of the PLLA/CHAp nanocomposite microspheres was the relatively high specific heat capacity of hydroxyapatite. According to Cruz et al (2005), the molar heat capacity (C p,m ) of HAp is 694 ± 68 J mol -1 K -1 in the temperature range 298-1298 K, which is much higher than that of PLLA, from 145.4 to 156.7 J mol -1 K -1 in the temperature range from 332.5K (T g ) to 480 K (T m ) (Pyda et al 2004;Malmgren et al 2006). Therefore, CHAp (a hydroxyapatite based ceramic) can be regarded as a huge energy reservoir to absorb laser energy.…”
Section: Comparison Of Fusion Behaviormentioning
confidence: 99%